PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS NASABAH TERHADPA LOYALITAS NABAH PEMBIAYAAN GRIYA BSM DI BANK MANDIRI SYARIAH KCP RANCAEKEK - Dian Arifani; Nuraeni Nuraeni (Masoem University, 2017)
This study aims to analyze the BSM Griya Financing at Bank Syariah Mandiri KCP Rancaekek the influence of Marketing Mix on Customer Loyalty. This research uses quantitative descriptive methods. The research data was obtained from the premiere data by distributing questionnaires to BSM Bank Syariah Mandiri Griya Financing customers Kanca Rancaekek and then processed with SPSS 23.The results showed that there was no significant effect between the Marketing Mix on the Loyalty of BSM Griya Financing Customers in Bank Syariah Mandiri Kanca Rancaekek. This can be seen from the correlation coefficient of 0.212 with a significance of 0.064. Which means that between the variable Marketing Mix to Customer Loyalty is weak and insignificant.While the coefficient of determination of 4.5% means that the marketing mix only contributes a weak influence on the loyalty of BSM Griya financing customers by 4.5% and theremaining 95.5% is influenced by other factors not examined such as service quality.This research reveals that customers expect more attractive promotional activities. Customers also expect increased handling of complaints that arise and of course with appropriate solutions.